The use of web services and technologies in libraries. Trends and prospects - M. E. Drazkaja (Библиосфера)
The author considers the factors influening the use of the web technologies in libraries. The necessity to create a model of library technological processes strategic development accounting their convergence with the web technologies is substantiated.